2020
DOI: 10.1002/cti2.1153
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of animal models to understanding the role of the immune system in human idiopathic pulmonary fibrosis

Abstract: Pulmonary fibrosis occurs in a heterogeneous group of lung disorders and is characterised by an excessive deposition of extracellular matrix proteins within the pulmonary interstitium, leading to impaired gas transfer and a loss of lung function. In the past 10 years, there has been a dramatic increase in our understanding of the immune system and how it contributes to fibrogenic processes within the lung. This review will compare some of the models used to investigate the pathogenesis and treatment of pulmona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 127 publications
0
17
0
Order By: Relevance
“…Data supports that pulmonary fibrosis is the final result of previous alveolitis with excessive scarring (19,52,53). Current knowledge about IPF has been derived from detailed pathological analysis of human lung samples that elucidated its unique morphological characteristics, together with observations derived from animal models of disease (26,52,54,55). New insights raised from genetic and transcriptomic studies on IPF samples have given a better comprehension of the molecular and cellular mechanisms determining the lung phenotype of IPF and patient therapeutics (25,54,56).…”
Section: Mechanisms Of Ptx3 In Idiopathic Pulmonary Fibrosis: Interpreting Data From Ipfmentioning
confidence: 95%
See 1 more Smart Citation
“…Data supports that pulmonary fibrosis is the final result of previous alveolitis with excessive scarring (19,52,53). Current knowledge about IPF has been derived from detailed pathological analysis of human lung samples that elucidated its unique morphological characteristics, together with observations derived from animal models of disease (26,52,54,55). New insights raised from genetic and transcriptomic studies on IPF samples have given a better comprehension of the molecular and cellular mechanisms determining the lung phenotype of IPF and patient therapeutics (25,54,56).…”
Section: Mechanisms Of Ptx3 In Idiopathic Pulmonary Fibrosis: Interpreting Data From Ipfmentioning
confidence: 95%
“…Bleomycin (BLM) is vastly used to investigate the mechanisms involved in lung fibrosis in mice, and also in the selection of therapeutic drugs for IPF, including Pirfenidone and Nintedanib (25,26). Several studies have addressed the relevance of PTX3 in different models of pulmonary fibrosis (27)(28)(29).…”
Section: Ptx3 and Lung Fibrosis: Lessons From Experimental Models Of Pulmonary Fibrosismentioning
confidence: 99%
“…This widely-characterized model recapitulates at day 14 after BLM instillation many features of human lung fibrosis i.e. collagen deposition within the alveolar interstitium, a thickening of the alveolar walls and masses of fibrosing-type lesions on the lung surface [ 27 ]. In our experimental conditions, no significant aggravating effect of IH on lung fibrosis severity was observed by histological analysis in mice Co-challenged with IH and BLM.…”
Section: Discussionmentioning
confidence: 99%
“…Single cell analysis included an average of 2396 cells for 1 mm core, 10337 for 2 mm core and 40904 for the whole section. By high dimensional analysis, the number of clusters found were respectively 12, 12, 13, 13 (1mm core), 17,15,17,18 (2 mm core) and 22 (whole slide). Clusters comprising sparse cells, such as Macrophages (Fig.…”
Section: Tma Validationmentioning
confidence: 99%
“…We have applied the MILAN high-plex technique 13 to a murine model of bleomycin-induced (BLM) lung brosis. This animal model is the most used in preclinical studies 14 and, in this context, the American Thoracic Society (ATS) has suggested guidelines to ensure that in vivo animal modeling studies have the highest chance of discriminating between potentially effective and ineffective anti brotic compounds [15][16][17] .…”
Section: Introductionmentioning
confidence: 99%